PEMBELAJARAN CERITA PENDEK BERBASIS KECAKAPAN HIDUP (KECUP) PASCA COVID-19 - sukatno (Badan Perencanaan Pembangunan Daerah dan Penelitian dan Pengembangan Kabupaten Wonogiri, 2023)
Identification the implementation of teaching learning after covid 19, describe the problems, and solutions to face the problems in identification the intrinsic of short story based on the life skills of the students on IX grades SMPN 2 Girimarto in the first semester 2023/2024. This writing use descriptive method. It is describe the phenomenon include the actually event and data in teaching learning after covid 19. There are the problems in teaching learning after covid 19 based on the life skills. The problems can be solving in the implementation in learning. The student's learning outcomes are good from 29. 2 students get 76-80, 6 students get 81-85, 7 students get 86-90, 9 students get 91-95, and 5 students get 96-100. Based on the data above it can be conclude that the teaching leaning activity is success.